Urinary Markers of Fibrosis and Risk of Cardiovascular Events and Death in Kidney Transplant Recipients: The FAVORIT Trial. Issue 10 (26th April 2017) - Park, M.; Katz, R.; Shlipak, M. G.; Weiner, D.; Tracy, R.; Jotwani, V.; Hughes‐Austin, J.; Gabbai, F.; Hsu, C. Y.; Pfeffer, M.; Bansal, N.; Bostom, A.; et al.
Abstract : Cardiovascular risk remains high in kidney transplant recipients (KTRs) despite improved kidney function after transplant. Urinary markers of kidney fibrosis and injury may help to reveal mechanisms of this risk. In a case–cohort study among stable KTRs who participated in the FAVORIT trial, we measured four urinary proteins known to correlate with kidney tubulointerstitial fibrosis on biopsy (urine alpha 1 microglobulin [α1m], monocyte chemoattractant protein‐1 [MCP‐1], procollagen type I [PINP] and type III [PIIINP] N‐terminal amino peptide) and evaluated associations with cardiovascular disease (CVD) events (n = 300) and death (n = 371). In adjusted models, higher urine α1m (hazard ratio [HR] per doubling of biomarker 1.40 [95% confidence interval [CI] 1.21, 1.62]), MCP‐1 (HR 1.18 [1.03, 1.36]), and PINP (HR 1.13 [95% CI 1.03, 1.23]) were associated with CVD events. These three markers were also associated with death (HR per doubling α1m 1.51 [95% CI 1.32, 1.72]; MCP‐1 1.31 [95% CI 1.13, 1.51]; PINP 1.11 [95% CI 1.03, 1.20]). Higher concentrations of urine α1m, MCP‐1, and PINP may identify KTRs at higher risk for CVD events and death. These markers may identify a systemic process of fibrosis involving both the kidney and cardiovascular system, and give new insights into mechanisms linking the kidney with CVD. Abstract : In a case‐cohort study within the FAVORIT trial, researchers measure urine biomarkers of kidney fibrosis and injury and find an association with cardiovascular risk and mortality.